Aging and the evolution of comorbidities among HIV-positive individuals in a European cohort. (23rd October 2018) - Pelchen-Matthews, Annegret; Ryom, Lene; Borges, Álvaro H.; Edwards, Simon; Duvivier, Claudine; Stephan, Christoph; Sambatakou, Helen; Maciejewska, Katarzyna; Portu, José Joaquín; Weber, Jonathan; Degen, Olaf; Calmy, Alexandra; et al.
Abstract : Objectives: To describe changes in the prevalence of comorbidities and risk factors among HIV-positive individuals in the EuroSIDA study. Design: Comparison of two cross-sectional cohorts of HIV-positive adults under active follow-up in 2006 and 2014. Methods: Baseline demographics and prevalence of comorbidities were described. Factors associated with the prevalence of chronic kidney disease (CKD) and cardiovascular disease (CVD) were assessed by logistic regression modelling using generalized estimating equations. Results: Nine thousand, seven hundred and ninety-eight individuals were under active follow-up in EuroSIDA during 2006 and 12 882 during 2014. Compared with study participants in 2006, those in 2014 were older [median age 48.6 years (IQR 40.3–55.1) vs. 43.1 years (37.2–50.0) in 2006] and had higher prevalence of hypertension (59.6 vs. 47% in 2006), diabetes (6.3 vs. 5.4%), CKD (6.9 vs. 4.1%) and CVD (5.0 vs. 3.7%). Individuals in the 2014 cohort had higher odds for CKD (unadjusted OR 2.62, 95% CI 2.30–2.99, P  < 0.0001) and CVD (OR 1.88, CI 1.68–2.10, P  < 0.0001), but after multivariable adjustment for age group, comorbidities and other factors, year of cohort was no longer significantly associated with the odds of CKD [adjusted OR (aOR) 0.97, CI 0.52–1.82, P  = 0.92) or of CVD (aOR 0.94, CI 0.54–1.63, P  = 0.82). Conclusion: Between 2006 and 2014, the population aged and experienced an overall higher prevalence of non-AIDS comorbidities, including CKD and CVD. The increase in CVD could be explained by the aging population, and the increase in CKD by aging and changes in other factors. Treatment strategies balancing HIV outcomes with long-term management of comorbidities remain a priority.